SIFAT FISIS DAN KIMIA BRIKET ARANG CAMPURAN LIMBAH KAYU GERGAJIAN DAN SABETAN KAYU - Djeni Hendra; Ina Winarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Briquetted charcoal was experimentally manufactured using the mixture of sawdust and woody slab wastes as the main materials. At first, sawdust wastes were carbonized in a semi-continuous kiln into the sawdust charcoal. Meanwhile, carbonized on woody slab wastes was conducted in a drum kiln yielding the slab charcoal. Further, the resulting sawdust charcoal and slab charcoal were mixed in varying respective portion, i.e. consecutively : (80% and 20%; 60% and 40%; 50% and 50%; 40% and 60%). The mixture was subsequently added with tapioca flour as binding agent at 5 percent, then molded, and compressed under 30-ton hydraulic pressure into the briquetted charcoal. In addition, the briquetted charcoal was also correspondingly prepared from I 00 percent sawdust, and regarded as with 0-percent woody slabs (i.e.100% and 0%). Such mixture in varying portions was further asserted as treatment. The resulting briquette charcoal was subsequently examined of its physical and chemical properties, i.e. moisture content, ash content, volatile matter, fixed carbon, density, compressive strenght, and caloric values.The result revealed that the recovery/yield sawdust charcoal was about 24.57-29.16 percent, while that of slab charcoal was 25.26-39.20 percent. Further, the mixture of sawdust charcoal and slabs charcoal at 40% : 60% portion brounght out the briquetted charcoal with the most satisfactory physical and chemical properties i.e. the moisture content of the briquette charcoal was in the range of 2.50-4.12 percent, ash content 13.22-21.41 percent, volatile matter 20.22-21.94 percent, fixed carbon content 56.65-66.36 percent, density 0.412-0.487 gram per cm3, compressive strenght 16.43-38.13kg per cm2, and caloric value 4515-5834 cal per gram.